Bacterial Diversity of the Gastric Content of Preterm Infants during Their First Month of Life at the Hospital - Moles, Laura; Gómez, Marta; Jiménez, Esther; Bustos, Gerardo; de Andrés, Javier; Melgar, Ana; Escuder, Diana; Fernández, Leónides; del Campo, Rosa; Rodríguez, Juan Miguel (Frontiers in Nutrition, 2017)
Studies focused on the stomach microbiota are relatively scarce, and most of them are focused on the adult population. The aim of this work is to describe the bacterial communities inhabiting the gastric content (GC) of preterm neonates. For that purpose, GC samples were collected weekly from a total of 13 preterm neonates during their first month of life within their hospital stay. Samples were analyzed by using both culture-dependent and -independent techniques. The former allowed the isolation of bacteria belonging mainly to the genera Enterococcus, Staphylococcus, Streptococcus, Serratia, Klebsiella, and Escherichia. The cultured dominant species in the GC samples during all the hospitalization period were Enterococcus faecalis and Staphylococcus epidermidis. Multilocus sequence typing (MLST) analysis revealed the presence of high-risk clonal complexes associated with the hospital environment, which may colonize enteral feeding tubes. Similarly, the 16S rRNA sequencing showed that Streptococcus, Staphylococcus, Lactobacillus, Enterococcus, Corynebacterium, and Propionibacterium were the dominant genera present at 75% of the gastric samples. However, the genera Serratia, Klebsiella, and Streptococcus were the most abundant. Own mother’s milk (OMM) and donor milk (DM) were collected after their pass through the external feeding tubes to assess their bacterial content. OMM and DM had a similar bacterial pattern to GC. Based on these data, the GC of preterm neonates is dominated by Proteobacteria and Firmicutes and harbors high-risk bacterial clones, which may colonize enteral feeding tubes, and therefore the feeds that pass through them.